Phonecards used by companies as media for its coffee products in Brazil: Coffee images in phonecards - de Souza Tavares, Wagner (Journal of Gastro Tourism, 2025)
The aim was to identify phonecards circulated in Brazil with prints associated with coffee as well as their number and use by companies as advertising means for coffee brands. The study was carried out in a phonecard collection in Sete Lagoas, Minas Gerais, Brazil. The front and back of the cards were analyzed. Images of 23 different coffee brands were printed on 25 phonecards, which were produced in 1997, 1999 and 2000, with the month with the highest number of cards produced being January 2000, with nine. Print runs of 5,000, 10,000 and 16,000 were identified with the first being the prevalent one with 19 cards. The front of the cards was printed with images of company logos, branches with ripe coffee beans, bags with coffee brand names, certification stamps, and coffee cups, while the back with the company address and telephone and fax numbers. Coffee companies, mostly from the states of Bahia and Minas Gerais displayed their product images on phonecards as means of visual communication and advertising to other regions. The interest in the production of phonecards suggests that this form of product marketing financially benefited coffee producers in Brazil.